Consumer Behaviour of Generation Z in the ‘Coffee’ Phenomenon at Cafes - Vidya Nindhita; Ni Putu Rizky Arnani (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kabupaten Sragen, 2025)
Consumer behavior refers to the analysis of consumer decision choices to buy a product. Generation Z is a generation that has unique characteristics in consumer behavior, especially in the growing coffee phenomenon. The high intensity of Generation Z in the style and lifestyle of enjoying coffee and hanging out in public spaces is of particular interest to researchers. Not only as a study of consumer behavior, but also for the benefit of business development from the business side. This research wants to reveal how consumer behavior in Generation Z in the phenomenon of drinking coffee in cafes. This research uses qualitative research methods with six informants who were selected using purposive sampling technique with ages that include Generation Z and have the habit of drinking coffee in cafes in a certain intensity. The results showed that the main themes were divided into background, consumer characteristics, considerations, and social media. Generation Z's considerations in choosing a café are obtained through ambience, live music, facilities, interior design, space planning context, budget, distance, and rating. It is interesting that Generation Z is synonymous with social media, but in this study there is no desire to present themselves on social media through their coffee habit.